2022
DOI: 10.1039/d1tc04028f
|View full text |Cite
|
Sign up to set email alerts
|

TADF: Enabling luminescent copper(i) coordination compounds for light-emitting electrochemical cells

Abstract: The last decade has seen a surge of interest in the emissive behaviour of copper(I) coordination compounds, both neutral compounds that may have applications in organic light-emitting doides (OLEDs) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 160 publications
(380 reference statements)
7
84
1
1
Order By: Relevance
“…[Cu(P^P)(N^N)] + complexes are more usually associated with their emissive properties and are of particular interest because of their ability to exhibit thermally-activated delayed fluorescence (TADF). 231 DSCs containing [Cu(POP)(1)] + and an I 3 − /I − redox mediator gave very low PCEs (<0.1%) due to low values of both V OC and J SC , even in the presence of cheno. 232 Other [Cu(P^P)(N^N)] + complexes that have been trialled in DSCs include [Cu(PPh 3 ) 2 (61)][PF 6 ] and [Cu(PPh 3 ) 2 (62)][PF 6 ].…”
Section: The Most Readily Achieved Goal: Copper-based Sensitizers In ...mentioning
confidence: 99%
“…[Cu(P^P)(N^N)] + complexes are more usually associated with their emissive properties and are of particular interest because of their ability to exhibit thermally-activated delayed fluorescence (TADF). 231 DSCs containing [Cu(POP)(1)] + and an I 3 − /I − redox mediator gave very low PCEs (<0.1%) due to low values of both V OC and J SC , even in the presence of cheno. 232 Other [Cu(P^P)(N^N)] + complexes that have been trialled in DSCs include [Cu(PPh 3 ) 2 (61)][PF 6 ] and [Cu(PPh 3 ) 2 (62)][PF 6 ].…”
Section: The Most Readily Achieved Goal: Copper-based Sensitizers In ...mentioning
confidence: 99%
“…However, it has been observed that the presence of stericallydemanding groups may affect compound stability in solution with respect to dynamic ligand exchange. 14 Overviews of [Cu(N^N)(P^P)] + emitters 10,11 reveal that some of the most efficient copper-based LECs have been fabricated using [Cu(6,6′-Me 2 bpy)(xantphos)][PF 6 ], 15 [Cu(4,5,6-Me 3 bpy) (xantphos)][PF 6 ], 16 and [Cu(4,4′-(CF 3 ) 2 -6,6′-Me 2 bpy) (xantphos)][PF 6 ]. 17 Compounds for which high values of the solid-state photoluminescence quantum yields (PLQYs) have been found include [Cu(4,4′,6,6′-Me 4 bpy)(POP)][BF 4 ] (55% or 74%, depending on whether the sample was ground), 18 [Cu(6-Mebpy)(xantphos)][PF 6 ] (34%), 15 [Cu(6-Etbpy)(xant-phos)][PF 6 ] (37%), 15 and [Cu(6,6′-Me 2 bpy)(xantphos)][PF 6 ] (37% 15 or 62%, 19 the difference again being attributed to sample morphology).…”
Section: Introductionmentioning
confidence: 99%
“…59,62 We have previously demonstrated that [Cu(POP)(N^N)][PF6] and [Cu(xantphos)(N^N)][PF6] compounds, in which the N^N ligand is bpy or a methyl-substituted derivative, exhibit TADF. 20,63 Currently the operational model of a LEC is described both by the electrochemical doping model (ECDM) and the electrodynamic model (EDM). Both theoretical mechanisms rely on mobile ions in the active layer.…”
Section: Introductionmentioning
confidence: 99%